2014
DOI: 10.1016/j.neuropharm.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and HIV-1-induced neurotoxicity: Role of trace amine associated receptor 1 cAMP signaling in astrocytes

Abstract: Methamphetamine (METH) is abused by about 5% of the United States population with approximately 10–15% of human immunodeficiency virus-1 (HIV-1) patients reporting its use. METH abuse accelerates the onset and severity of HIV-associated neurocognitive disorders (HAND) and astrocyte-induced neurotoxicity. METH activates G-protein coupled receptors such as trace amine associated receptor 1 (TAAR1) increasing intracellular cyclic adenosine monophosphate (cAMP) levels in presynaptic cells of monoaminergic systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 59 publications
1
76
0
1
Order By: Relevance
“…Alternatively, as TAAR1 is expressed in the layer V of PFC, where significant deficiency in NMDA receptor-mediated glutamate transmission was observed, it is possible that glutamate transmission deficits could be a direct consequence of the absence of cortical TAAR1. Intriguingly, a recent report indicated that TAAR1 can modulate the function of the glutamate transporter EAAT2 leading to alterations in glutamate clearance suggesting a direct connection between TAAR1 and glutamate transmission (Cisneros and Ghorpade, 2014). Finally, we cannot exclude an involvement of other monoaminergic systems and signaling pathways (ie, serotonin-mediated, (Lindemann et al, 2008)) that might be involved in TAAR1-mediated functions and behaviors.…”
Section: Discussionmentioning
confidence: 65%
“…Alternatively, as TAAR1 is expressed in the layer V of PFC, where significant deficiency in NMDA receptor-mediated glutamate transmission was observed, it is possible that glutamate transmission deficits could be a direct consequence of the absence of cortical TAAR1. Intriguingly, a recent report indicated that TAAR1 can modulate the function of the glutamate transporter EAAT2 leading to alterations in glutamate clearance suggesting a direct connection between TAAR1 and glutamate transmission (Cisneros and Ghorpade, 2014). Finally, we cannot exclude an involvement of other monoaminergic systems and signaling pathways (ie, serotonin-mediated, (Lindemann et al, 2008)) that might be involved in TAAR1-mediated functions and behaviors.…”
Section: Discussionmentioning
confidence: 65%
“…Such an effect has potentially significant functional consequences for Parkinson disease-related abnormalities. Interestingly, methamphetamine-induced activation of TAAR1 leads to intracellular cAMP accumulation in human astrocytes, an effect that decreased glutamate clearance abilities due to a downregulation of excitatory amino acid transporter 2 (EAAT-2) (Cisneros and Ghorpade, 2014). Although methamphetamine has a promiscuous pharmacology, molecular alterations in astrocyte TAAR1 levels also induced changes in EAAT-2 levels and function, consistent with the methamphetamine response being TAAR1 mediated (Cisneros and Ghorpade, 2014).…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 82%
“…Such a distribution is generally seen in both rodents and primates and is consistent with the effects of TAAR1-directed ligands described in other sections. At least in humans, expression may not be limited to neurons with one report of astrocytic TAAR1 (Cisneros and Ghorpade, 2014). Spinal cord expression may also occur, at least in rats (Gozal et al, 2014).…”
Section: B Trace Amine-associated Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…The location of TAAR1 expression is mostly intracellular in neurons (Miller, 2011) and also in glial cells (Cisneros and Ghorpade, 2014). Because the substances need to reach the location of expression of TAAR1 to bind to the receptor, the intracellular availability of the ligands is also relevant.…”
Section: Discussionmentioning
confidence: 99%